Research on the Gap Effect of Circular Concrete-Filled Steel Tubes Using the Improved Cohesive Zone Model - Jiang Yu; Bin Gong; Chenrui Cao (Applied Sciences, 2024)
Understanding the influence of gap distribution characteristics on the mechanical properties of circular concrete-filled steel tubes (CCFSTs) under bending load is important for stability and support design in engineering projects. In this study, the improved cohesive zone model considering friction was used to describe the mechanical behavior of mortar interfaces. Meanwhile, the concrete damage plastic model and isotropic elastoplastic model were applied for core concrete and steel tubes. The improved cohesive zone model has a unified potential function that governs the Mode I and Mode II failure processes of mortar interfaces to realize the mechanical interaction between concrete and steel. A smooth frictional function was utilized in the elastic stage to calculate the accurate frictional effect. Furthermore, the capability of the model in addressing unloading and reloading was verified, and the fracture energy varied accordingly during the cyclic loading. Then, the mechanical response of CCFSTs was investigated under bending loads by setting different gap sizes and angles between the gap and loading direction. The results show that under three-point bending, the equivalent plastic strains at the middle part of CCFSTs are much larger and the peak bearing forces are much lower than the other degrees when the angles between the coronal gap axis and loading direction equal 0° and 180°. In addition, the order of the peak bearing forces, from highest to lowest, is when the height of the coronal-cap gap increases from 0.0 mm to 2.5 mm, 5.0 mm, and 7.5 mm. The significant effect makes it inappropriate to ignore the weakening of the structural performance caused by coronal gaps in structural design.